Intergroup attitudes on intergroup behavioral intention among Somali clans in Somalia - Abdiaziz, Ahmed; Ma’rof, Aini Azeqa; Hamsan, Hanina H.; Abdullahi, Yasmin (Human Resource Management Academic Research Society, 2022)
Different social groups have different social relationship that are mostly characterized by prejudice and conflicts. Intergroup conflict usually attributed to negative behaviors between different groups that mainly underlies by mistrust, hostility, aggression, and discrimination. However, this study attempts to determine how one’s intergroup attitudes may affect their intention to behave to other group members; specifically, whether the level of social identification, out-group trust, prejudice, social distance, and perceived similarity may impact one’s intention to behave to other groups. A cross-sectional design method was used to employ quantitative approach via self-administered questionnaire. For the purpose of this study, the Somali Noble group living in Waberi district was chosen as the sample. The results indicate that all intergroup attitudes were significantly correlated with intergroup behavioral intention. Specifically, social distance and outgroup trust positively correlated with intergroup behavioral intention, meanwhile, negative significant correlations were reported between social identification, prejudice, and perceived similarities with intergroup behavioral intention. The result also indicates that the Somali Nobel group has a lower level of trust for Somali Bantu, which explains their lack of desire to socialize with the Bantu clan. The main indicators that contribute to intergroup behavioral intention were outgroup trust, social distance and perceived similarity with social distance was the unique contributor. The theoretical and practical implications from the Social Identity Theory and Contact Hypothesis were discussed.